Dialektika Islam dan Budaya dalam Pendekatan Teologis-Historis dan Filosofis - Ibnu Ali; Moh. Soheh; Mujiburrohman (Kariman: Jurnal Pendidikan Keislaman, 2023)
The presence of Islam among humans has been going on for more than fourteen centuries. During that time Islam has been contributing to the dynamics of human progress. But Islam is also often contrasted with culture. Islam is considered to have originated from Arab so that Islam is not opened up by other culture. This paper will try to provide a dialectical analysis of answers between Islam and culture through theological, historical and philosophical approaches. That ontologically and epistemologically, Islam is a doctrine that originates from revelation, while culture is the embodiment of work, creativity and taste that originates from human reason. Islam as a religion is presented to humans so that they experience assimilation contact with Arabic culture at first and then with other cultures. But Islam is not synonymous with Arabic culture. The two can still be distinguished, although they cannot be separated. Because comprehending Islam must go through Arabic as the language of revelation and its social context. However, Islam accepts the plurality of cultures so that it can be present and accepted in all human cultures because Islam is presented for all human beings.